The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/rausp-08-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Advisor gender and advice justification in advice taking

Abstract: Purpose The purpose of this paper is to identify under what circumstances advisor gender and advice justification influence advice taking by managers. Design/methodology/approach The authors designed a quasirational managerial decision experiment with both analytic and intuitive cues. The design was a 2 × 2 between-subjects factorial, in which gender (male/female) and advice justification (intuitive/analytic) were crossed. The experiment involved two independent samples, taken from Amazon Mechanical Turk wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Third, good justifications can also increase utilization. Participants in two studies that manipulated whether advice was justified by formal analysis or instead by intuition tended to prefer the former, utilizing advice justified by intuitions only when they had strong reasons to believe that said intuitions were well-founded (Ribeiro et al, 2020†; Tzioti et al, 2014†). In another study, participants reported preferring additional information about the alternatives over direct recommendations for or against actions, likely because it helped them improve decision accuracy and maintain decision autonomy (Dalal & Bonaccio, 2010‡).…”
Section: Stage 2: Advice Utilizationmentioning
confidence: 99%
“…Third, good justifications can also increase utilization. Participants in two studies that manipulated whether advice was justified by formal analysis or instead by intuition tended to prefer the former, utilizing advice justified by intuitions only when they had strong reasons to believe that said intuitions were well-founded (Ribeiro et al, 2020†; Tzioti et al, 2014†). In another study, participants reported preferring additional information about the alternatives over direct recommendations for or against actions, likely because it helped them improve decision accuracy and maintain decision autonomy (Dalal & Bonaccio, 2010‡).…”
Section: Stage 2: Advice Utilizationmentioning
confidence: 99%